Sams teach yourself SAP in 24 hours - Anderson, George W. (Software architect) (Sams, 2011)
The #1 hands-on SAP tutorial for beginners: now fully updated and 100% refocused on two key audiences: business users and IT professionals Now easier to read and more useful, with more actionable guidance, better screenshots, and better foundational material for beginners Reflects new SAP technologies and roadmaps, including SAP in the cloud Covers the full lifecycle: project management, installation, administration, usage - even SAP careers Step-by-step instructions, case studies, exercises, and tips In just 24 sessions of one hour or less, beginning-to-intermediate-level managers and IT pro master the latest version of SAP, and learn how to use it in real business environments. You learn hands-on, step-by-step, through practical examples based on SAP's free demonstration software. This edition has been fully reorganized and updated to help business and technical readers quickly learn what they need to know, and to help absolute beginners move forward more rapidly. Each chapter is built around a real-world case study that helps you put your new knowledge to the test. Long-time SAP consultant George Anderson explains SAP's goals, functionality, roles, and implementation considerations; NetWeaver, SAP ERP, and the SAP Business Suite; SAP's user interface; core SAP business tasks; reporting and querying; extending SAP with Microsoft Duet; managing implementations; using Basis; developing new applications; day-to-day administration; enhancements, upgrades, replatforming, cloud services, and more. Each lesson builds on what you've already learned, delivering a strong real-world foundation for success with SAP in any organization.